Effect of Terbium Additions on Microstructural, Thermal and Mechanical Properties of Eutectic Sn-3.5Ag Pb- Free Solder for Low Cost Electronic Assembly - Shalaby, Rizk Mostafa; Ibrahim, Fatma Elzahraa; Kamal, Mostafa (JOURNAL OF ADVANCES IN PHYSICS, 2019)
This work methodically concentrated on the effect of a trace amount of rare earth element terbium, Tb (0.1, 0.2, 0.3, 0.4 and 0.5 wt. %) on the properties of eutectic Sn-3.5 wt. %Ag were studied. The results indicated that addition of Tb rare earth can be refined the microstructure of the solder and intermetallic compound (IMC) Ag3Sn phase appeared in the solder matrix. Add a few quantity of rare earth Tb enhances the hardness and strength of eutectic Sn-Ag lead free solder joint. Also, results indicate that adding Tb to the eutectic Sn-3.5Ag remarkably enhances solderability, reliability, thermal and mechanical properties. It is also found that increasing in mechanical strength can depend on crystalline size refining in addition to some regular precipitates from IMC, Ag3Sn.